Built identifier for the control circuit subject - Legotkina, T. S.; Antineskul, A. V.; Gorozhankin, A. I. (2017 XX IEEE International Conference on Soft Computing and Measurements (SCM), 2017)
In work, the main attention is paid to the creation of the rule base, considered uniform and Chebyshev's distributions governed and concrete examples for the purpose of determination of the accuracy of modeling (approximation). Researchers showed that Chebyshev's distributions of the rule base, as compared with uniform distribution, gives a big accuracy when using an identical number of rules and approximately identical accuracy using a smaller number of rules. For example, in this article were considered one-port and multiport systems. The received precision characteristics for multiport systems were confirmed.